VIDA DE ESTUDANTE: um estudo sobre as microterritorialidades dos estudantes da UFMS/CPTL em Três Lagoas - MS - LARISSA DOS SANTOS CAMPOS (2021)
The work was developed as part of a master's research in Geography of the Postgraduate Program of the Federal University of Mato Grosso do Sul, Três Lagoas Campus and is linked to the Laboratory of Urban and Territory Studies - LETUR/UFMS. Our central objective was to analyze the role of students from the Federal University of Mato Grosso do Sul who live in the city of Três Lagoas in the production of micro-territories, through the apprehension and analysis of their daily spatial practices. From the methodological point of view, we followed mainly qualitative methodology instruments. We conducted interviews with semi-structured scripts with students face-to-face in the first stage and remotely during the period of the COVID 19 Pandemic. Combined with the interviews, field observations were made during the research, recorded in a field notebook. From the quantitative point of view, we gathered data and information about the post-graduate and graduate courses at UFMS and about the students in the academic department. Through the analysis of the students' spatial practices related to studying, living, consuming, and leisure (they are imbricated in the reality lived) we verified the strategies outlined in the university daily life for the production of micro-territorialities in the city guided by the identity constituted among the students; the university is constituted as a starting point for the realization of the life of these social subjects in the city. Some problems related to urban infrastructure were evidenced, especially mobility difficulties in the city (when there is dependence on public transportation), the strategy to "get around" this is the strengthening of group activities among students in specific places, which generates and strengthens some micro-territorialities in bars, dorms and spaces within the university itself that are shaped by students and are permeated with their meanings.